Enhancing Microwave Disinfection: Impact of Sodium Chloride on Microbial Inactivation - Saleh A. Alfawaz; Ibrahim N. Alquaydheb; Amirreza Ghadimi Avval; Sara Ghayouraneh; Samir M. El-Ghazaly; Jianhong Zhou; Yuchun Du (IEEE Access)
This study explores the role of sodium chloride (NaCl) in enhancing the efficiency of microbial inactivation using microwave energy with two distinct methods: temperature-controlled treatment and predefined cycle. The primary objective is to maintain a stable temperature within the biological samples during treatment. Detailed descriptions of the treatment system’s design and the function of each element are provided. Simulations are conducted to illustrate the heating behavior of liquids with and without NaCl, revealing significant differences in temperature profiles between the two media. The experimental design and the objective behind each iteration are discussed. The experimental design includes three different power levels to assess their impact on disinfection rates, with durations determined based on extensive preliminary experiments to identify the most effective combinations for microorganism elimination. The experiments aim to compare the efficiency of the temperature-controlled method and the predefined cycle in maintaining desired temperature ranges and enhancing microbial inactivation. A key aspect of the study is the significance of exposure time in temperature-controlled runs. It is observed that exposure time critically influences the inactivation performance, necessitating the design of predefined cycles to achieve more consistent and efficient microbial inactivation. Additionally, in this investigation, the system effectively disinfects three types of microorganisms: bacteria, viruses, and yeasts. The study also examines treatments across three different media to understand the influence of NaCl presence on microbial inactivation efficiency. These insights emphasize the critical importance of optimizing exposure time and incorporating NaCl in microwave-based disinfection processes to achieve more effective microbial inactivation.